Analysis of the Numeracy Literacy Ability of Aik Anyer State MTs Students in the Independent Learning Curriculum Era - Zuliyana, Anny (Jurnal Riset Ilmu Pendidikan, 2025)
Numeracy literacy skills play a crucial role in the current era of Independent Learning. With good mastery of numeracy literacy, students are able to think critically and solve various problems they face in everyday life. This study aims to evaluate the level of numeracy literacy of students during the Independent Learning era. The subjects were 20 students of MTs NW Aik Anyer, who have implemented the Independent Curriculum. The approach used in this study was a qualitative descriptive method. Data were collected through a five-question essay test that presented data, with numeracy literacy indicators including: 1) The ability to use various numbers and symbols related to basic mathematical operations to solve everyday problems; 2) The ability to analyze data in various formats (graphs, tables, charts, diagrams, etc.); and 3) The ability to interpret the results of the analysis to make predictions, formulate, and make decisions. Data were analyzed by calculating the average percentage for each numeracy literacy indicator. Based on the results of research and analysis of research data conducted by the researcher, the numeracy literacy skills of MTs NW Aik Anyer class students who have implemented the Independent Learning Curriculum are at a low level, namely 40%.